Nautilus The Biology and Paleobiology of a Living Fossil, Reprint with additions - Saunders, W. Bruce; Landman, Neil H.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2010)
This volume is a reprint of a classic book about Nautilus, first published in 1987, with an introductory chapter summarizing all of the work on Nautilus and its habitat since the publication of the first edition more than 20 years ago. The surge in articles in the last two decades indicates an expanded interest in the subject, reflecting a renewed appreciation of the complexity and fragility of the marine habitat and its biota. The 37 chapters are written by 48 experts in the field and cover all aspects of this living fossil from its ecology to its embryology. This volume also features new photos, including an impressive image of the first hatched Nautilus in captivity. Nautilus is an iconic animal in the marine realm and represents part of the diverse fauna of the Indo-Pacific. It is also a member of a lineage of shelled cephalopods dating back more than 400 million years. As a result, this volume will be relevant to the fields of marine science, evolutionary biology, and paleontology.
Nautilus Studies The First Twenty-Two Centuries -- Nautilus Studies The First Twenty-Two Centuries -- The Ancestry of the Genus Nautilus -- The Ancestry of the Genus Nautilus -- Nautilus and Its Distribution -- The Species of Nautilus -- Geographic Distribution of Nautilus Shells -- Genetic Variation and Phylogeny in Nautilus -- Morphological Variation in Nautilus from Papua New Guinea -- Biometrie Analysis of Nautilus pompilius from the Philippines and the Fiji Islands -- Biomineralization and Systematic Implications -- Ecology -- Ecology, Distribution, and Population Characteristics of Nautilus -- Incidence and Kinds of Epizoans on the Shells of Live Nautilus -- On the Habitat of Nautilus pompilius in Tañon Strait (Philippines) and the Fiji Islands -- Predation on Nautilus -- Physiology -- The Central Nervous System -- The Sense Organs of Nautilus -- Visual Behavior and Visual Sensitivity of Nautilus pompilius -- A Possible Function of the Iris Groove of Nautilus -- Histology of the Long Digital Tentacles -- The Functional Morphology of the Tentacle Musculature of Nautilus pompilius -- The Circulatory System -- The Excretory System of Nautilus -- Respiratory Physiology -- Mouth Part Histology and Morphology -- Metabolism -- Energy Metabolism of Nautilus Swimming Muscles -- Oxygen Conformity and Metabolic Arrest in Nautilus -- Ventilation and Oxygen Extraction by Nautilus -- Reproduction and Growth -- Reproduction and Embryology of Nautilus -- Development of the Embryonic Shell of Nautilus -- Growth and Longevity of Nautilus -- Adolescent Growth and Maturity in Nautilus -- The Shell and Its Architecture -- Nautilus Shell Architecture -- Ultrastructure of the Nautilus Shell -- Swimming and Buoyancy -- Locomotion of Nautilus -- Nautilus Shell Hydrostatics -- Buoyancy in Nautilus -- Aquarium Maintenance -- Collection and Aquarium Maintenance of Nautilus -- Experience with Aquarium Rearing of Nautilus in Japan -- A Small, Closed Aquarium System for Nautilus.
Keywords: Life sciences; Geography; Paleontology; Aquatic biology; Evolution (Biology).; Life Sciences; Freshwater & Marine Ecology; Paleontology; Earth Sciences, general; Evolutionary Biology